The Role of Green Innovation in Strengthening Green Economy Towards Sustainability Performance: MSMEs in Jumantono District, Karanganyar - Setyaningsih Setyaningsih; Dhimas Ridha Arrahman (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The main objective of this research is to analyze previous studies and assess the viability of companies by utilizing the triple bottom line approach, which takes into account economic, environmental, and social aspects. The expectation is that these metrics will provide an accurate representation of the present situation. The novelty of this study lies in introducing green innovation as a moderating variable that strengthens the influence of the green economy on sustainability performance. The study involved 81 MSMEs located in Jumantono District, Karanganyar. Information was gathered directly from participants through the use of survey tools. The analysis technique employed was Partial Least Squares (PLS). The research findings indicate that the application of green economy practices significantly enhances economic, environmental, and social performance. This implies that the more robust the implementation of green economy strategies, the better the outcomes in terms of business sustainability. Additionally, the study reveals that green innovation strengthens the relationship between green economy and both economic and environmental performance, serving as a reinforcing factor. However, green innovation does not exhibit a moderating effect in the relationship between green economy and social performance, suggesting that its impact in the social dimension may be limited or influenced by other variables not examined in this study. These findings suggest that green economy initiatives are effective in improving sustainability performance, particularly when supported by green innovation strategies. MSMEs are encouraged to adopt balanced economic, environmental, and social practices to enhance long-term sustainability.